Improvement of Dialysis Dosing Using Big Data Analytics - Mumtaz, Syeda Leena (2021)
A Master of Science thesis in Biomedical Engineering by Syeda Leena Mumtaz entitled, “Improvement of Dialysis Dosing Using Big Data Analytics”, submitted in April 2021. Thesis advisor is Dr. Abdulrahim Shamayleh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).